Hubungan Persepsi terhadap Harapan Orang Tua dan Ketakutan Akan Kegagalan pada Siswa SMA Negeri 17 Makassar - Wijaya, Citra Adelia; Nur, Haerani; Jalal, Novita Maulidya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the relationship between perceptions of parental expectations and fear of failure among students at SMA Negeri 17 Makassar. The sample in this study was 280 Makassar State High School students. This research uses a quantitative approach with the Spearman rho analysis technique. The results of the analysis obtained a significance value of 0.00 (p < 0.05) which shows that there is a relationship between perceptions of parental expectations and fear of failure in students at SMA Negeri 17 Makassar. The correlation value (r) obtained was 0.330, indicating that the correlation is positive, which means that the higher the perception of parental expectations, the higher the fear of failure. Students who perceive their parents' expectations as high will easily feel anxious due to fear of failure, while students who perceive their parents' expectations as low will not easily feel anxious so they will not experience fear of failure. It is hoped that the results of this research can contribute to the fields of developmental psychology and educational psychology and become a reference source that can provide information regarding the relationship between perceptions of parental expectations and students' fear of failure.